A combination of species distribution and ocean-biogeochemical models suggests that climate change overrides eutrophication as the driver of future distributions of a key benthic crustacean in the estuarine ecosystem of the Baltic Sea. (5th August 2020) - Gogina, Mayya; Zettler, Michael L; Wåhlström, Irene; Andersson, Helén; Radtke, Hagen; Kuznetsov, Ivan; MacKenzie, Brian R
Abstract: Species in the brackish and estuarine ecosystems will experience multiple changes in hydrographic variables due to ongoing climate change and nutrient loads. Here, we investigate how a glacial relict species ( Saduria entomon ), having relatively cold, low salinity biogeographic origin, could be affected by the combined scenarios of climate change and eutrophication. It is an important prey for higher trophic-level species such as cod, and a predator of other benthic animals. We constructed habitat distribution models based occurrence and density of this species across the entire Baltic and estimated the relative importance of different driving variables. We then used two regional coupled ocean-biogeochemical models to investigate the combined impacts of two future climate change and nutrient loads scenarios on its spatial distribution in 2070–2100. According to the scenarios, the Baltic Sea will become warmer and fresher. Our results show that expected changes in salinity and temperature outrank those due to two nutrient-load scenarios (Baltic Sea Action Plan and business as usual) in their effect on S. entomon distribution. The results are relatively similar when using different models with the same scenarios, thereby increasing the confidence of projections. Overall, our models predict a net increase (and local declines) of suitable habitat area, total abundance and biomass for this species, which is probably facilitated by strong osmoregulation ability and tolerance to temperature changes. We emphasize the necessity of considering multiple hydrographic variables when estimating climate change impacts on species living in brackish and estuarine systems.